Synthesis of (Z)-2-Alkylidene-4-oxothiazolidine Derivatives Under Microwave Irradiation - Shejul, Pravin B.; Kadam, Nitin H.; Vyavahare, Amol V.; Kasawar, Gajanan B.; Panpaliya, Prashant (Asian Journal of Chemistry, 2010)
In comparison to conventional technique, experimental evidence reveals the benefits of the microwave-promoted synthesis of functionalized 4-oxothiazolidine derivatives 4 in terms of simple workup, efficiency and safe reproducibility.